Cascading effects of seed-stem-individual spatial patterns along a grazing gradient - Qin-Yuan, Zhou; Quan-Min, Dong; Fang-Cao, Wang; Yu-Zhen, Liu; Bin, Feng; Xiao-Xia, Yang; Yang, Yu; Chun-Ping, Zhang; Quan, Cao; Wen-ting, Liu (Frontiers in Plant Science, 2023)
Studying the seed trait–stem trait–individual spatial pattern system is helpful for understanding the developmental direction of plant dynamics and populations under grazing disturbance as well as the antagonistic relationship between animals and plants, but few systematic analyses of this spatial pattern system have been carried out. Kobresia humilis is the dominant species in alpine grasslands. We studied K. humilis seed traits and their relationship with K. humilis reproductive individuals, the relationship between reproductive and vegetative stems, and the weights and spatial patterns of reproductive and nonreproductive individuals under four grazing treatments: no grazing (control), light grazing, moderate grazing and heavy grazing. We explored the relationship among seed size and seed number with reproductive stems and vegetative stems along the grazing gradient and assessed the spatial pattern changes between reproductive and nonreproductive individuals. The results showed the following: (1) Seed size increased with increasing grazing intensity, and the coefficient of variation for seed size and seed number in the heavy grazing treatment was greater than 0.6. (2) The structural equation model showed that grazing treatment had a positive effect on seed number, seed size and reproductive stem number and a negative effect on reproductive stem weight. (3) Grazing treatment did not affect the resource allocation to reproductive stems and vegetative stems per unit length of reproductive K. humilis individuals. (4) Compared with the number of reproductive individuals in the no grazing treatment, the number in the heavy grazing treatment decreased significantly, and the negative correlation between reproductive individuals and nonreproductive individuals changed from a full-scale negative correlation to a small-scale negative correlation and a large-scale positive correlation. Our study showed that grazing could activate and change the resource allocation pattern of dominant species in a grassland and have significant positive effects on reproductive stem number, reproductive stem weight, seed number and seed size. Along a grazing intensity gradient, with the increase in distance between reproductive and nonreproductive individuals, the transformation of intraspecific relationships from a negative correlation to a positive correlation is an ecological strategy conducive to population survival.